On Qualitatively New Productive Forces and Their Advantages for China (World Marxist Review, 2024)
Qualitatively new productive forces refer to material, technological and intellectual capabilities associated with a fourth industrial revolution and their potential to drive productivity growth and improvements in the satisfaction of human needs. In capitalist societies these transformations are associated with crises and waves of creative destruction raising the question as to whether a socialist polity can manage them in less destructive ways. In Capital Marx provided tools to analyse the turbulent implications of radical increases in productivity. At present Chinese public and private capital is playing a leading role in radical productivity growth and the development of new products (as part of a structural transformation designed to create new drivers of growth to replace older ones that have lost momentum). China’s progress poses a major competitive challenge for incumbents who are unable to match the price and quality of Chinese made goods. In the Collective West the fundamental problems derive from a secular decline in productivity growth since the 1970s itself due to a decline in the rate of profit, and financialisation. A response of the Collective West is to intensify its attempts to suppress China’s development. Their ultimate effectiveness is questioned.